2019
DOI: 10.21079/11681/33377
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Lidar and Radar Imaging System (CLARIS) lidar data report : 2011 - 2017

Abstract: Coastal Lidar and Radar Imaging System between 2011 and 2017 along the northern Outer Banks of North Carolina near the CHL Field Research Facility. The report briefly describes the system and study site as well as the survey data extents, collection dates, and environmental context and data access information for the point cloud and digital elevation model products. Initial morphology data products and initial analyses are presented including calculations of shoreline change, dune volume, beach volume, beach s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The CLARIS system also includes an IX-Blue ATLANS-C inertial navigation system (INS) with an integrated inertial measurement unit (IMU), wheel-mounted distance measurement instrument (DMI) and global navigation satellite system (GNSS) antennas (IXBlue 2016) ( Table 1). More details regarding the CLARIS instrumentation and capabilities can be found in Spore et al (2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLARIS system also includes an IX-Blue ATLANS-C inertial navigation system (INS) with an integrated inertial measurement unit (IMU), wheel-mounted distance measurement instrument (DMI) and global navigation satellite system (GNSS) antennas (IXBlue 2016) ( Table 1). More details regarding the CLARIS instrumentation and capabilities can be found in Spore et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…MTL allows for the collection of dense point clouds (typically 100+ points/m 2 ) * that capture both the bare earth surface and objects above or obscuring the bed surface, such as vegetation, infrastructure, and people. Past research in coastal systems has used MTL to monitor beach nourishment performance (e.g., Pietro et al 2008), cliff erosion, and regional scale subaerial beach and dune morphology (Donker et al 2018;Spore et al 2019). Fixed station (tripod-based) terrestrial lidar scanning (FTL) has also widely been utilized for providing valuable new insights on coastal dune dynamics on sub-meter spatial scales and at time scales of months to years (Brodie et al 2019;Conery et al 2019;Danchenkov et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous observations and numerical simulations have shown that winds may alter water levels in the sound by more than 2 m, a magnitude that surpasses the tidal range within the sound by at least an order of magnitude (Clunies et al, 2017;Mulligan et al, 2015;Rey & Mulligan, 2021;Safak et al, 2016). Spore & Brodie, 2017;Spore et al, 2019). The seabed elevation data were merged with historical elevation data (Stockdon et al, 2013) to create an updated and continuous 10 m resolution digital elevation model (DEM) of the Oregon Inlet system that includes the main ebb channel, the flood and ebb tidal deltas, various channels incising those deltas, and the beach and dunes adjacent to the inlet (Figure 1c).…”
Section: Study Sitementioning
confidence: 98%
“…All the above data collection did take place in idealized conditions at a location that operators were familiar with (Fischer et al 2019). Whereas this collect had fairly square coverage over the <1 km 2 AOI that included different land cover types, other coastal terrain collects may demand narrower collects that can lead to SfM issues, due to bowl effects (e.g., James and Robson 2014;Jaud et al 2019;Renaud et al 2019) or additional homogeneity in sandy areas (Seymour et al 2017). As a result, there may be reduced accuracy with GCP dismissal.…”
Section: Usace Data Applicability Examplementioning
confidence: 99%
“…The entirety of the FRF beach-dune system was scanned with the Coastal Lidar and Radar Imaging System (CLARIS), a van-mounted Riegl VZ-2000 terrestrial lidar scanner coupled to an IX-Blue ATLANS-C inertial navigation system on 15 June 2017. The system and its operation are described in Spore and Brodie (2017), Spore et al (2019), andConery et al (2020). The system was capable of collecting elevation data from the approximate location of the dune crest to the shoreline utilizing a mobile 3D scanning pattern (radar mode) with similar accuracies described in Conery et.…”
Section: Mobile Terrestrial Lidar (Mtls) Controlmentioning
confidence: 99%